Moebius syndrome: clinical features, diagnosis, management and early intervention. Issue 1 (December 2016) - Picciolini, Odoardo; Porro, Matteo; Cattaneo, Elisa; Castelletti, Silvia; Masera, Giuseppe; Mosca, Fabio; Bedeschi, Maria
Abstract Background Moebius syndrome (MBS) is rare disease characterized by nonprogressive congenital uni- or bi-lateral facial (i. e. VII cranial nerve) and abducens (i. e. VI cranial nerve) palsy. Although the neurological and ophthalmological findings are quite well-known, data concerning the attendant functional difficulties and their changes over time are seldom addressed. In this study we attempt to estimate the prevalence of clinical and functional data in an Italian cohort affected by MBS. Methods The study included 50 children, 21 males and 29 females, aged 1 month to 14 years. The patients entered into a multidisciplinary diagnostic and follow-up protocol that had the specific purpose of detecting clinical and developmental deficits related to MBS. Results Involvement of the VII cranial nerve (total/partial, bilateral or unilateral) was present in 96 % of patients, and of the VI nerve in 85 %. Two patients were without impairment of the VII nerve and seven patients had no involvement of the VI nerve and were thus classified as Moebius-like because of the involvement of other CNs. Additional affected CNs were numbers III-IV in 16 %, V in 11 %, VIII and X each in 8 %, the XI in 6 %, the IX, most often partially, in 22 %, and the XII in 48 % of cases. Their development was characterized by global delay at one year of age, motor, emotional and speech difficulties at two years of age, a trend toward normalization at three years of age but with weakness in hand-eye coordination, and achieving average results at five years of age. Overall 90 % of children had a normal developmental quotient whereas only 10 % manifested cognitive deficits. Conclusion Early rehabilitation may enhance the recovery of normal function, particularly in vulnerable areas of development. It is possible that early intervention that integrates sensory and visual information with emotional difficulties can improve the prognosis of the child with MBS.